(untitled) (The International Journal for Scientific Research, 2024)
The Personal Data Protection Law in Saudi Arabia aims to protect individuals’ data and regulate businesses that collect, retain, analyze, process, and share it across borders around the globe. Artificial intelligence and data protection are interconnected concepts since AI uses data sets to make decisions and perform activities. However, ethical questions about personal data use and potential bias in AI persist in the present AI environment. Therefore, while AI has led to digital transformation in sectors like transportation, healthcare, and finance, the technology has privacy implications that limit its usage by many organizations. In the country’s journey to reduce its oil dependency and become modernized, it is significant for Saudi Arabia to have a sufficient set of regulations and laws to deal with AI-related legal challenges. In this regard, the authorities have initiated programs to streamline the KSA’s data protection laws with European AI regulations and data safety laws after recognizing the need to preserve data sets. This paper examines the present laws and legal regulatory framework for AI and data protection in Saudi Arabia and the legal challenges to protecting data in AI. The paper also discusses legal issues related to AI data protection and the barriers that restrict data protection law reform in light of the available literature on AI data protection. After examining the present data protection measures in the KSA, the paper gives recommendations for improving the overall AI data protection laws and regulations in the kingdom.